Pengaruh Persepsi Kualitas Pelayanan, Harga, dan Promosi terhadap Loyalitas Pelanggan di Café Njajan.Co - Sari Wiyanti; Bisma Reza Tresna Pamungkas; Toat Nur Alimudin; A Muahhammad Irsyad Syaril Aalaai (Institut Nalanda, 2024)
This study aims to examine the influence of perceived service quality, price, and promotion on customer loyalty at Café Njajan.co. The independent variables analyzed in this study include perceived service quality, price, and promotion, while customer loyalty is the dependent variable. The research uses a survey method with a quantitative approach, and data were collected through questionnaires distributed to 101 customers of Café Njajan.co. The data analysis technique applied is multiple linear regression. The results show that, collectively, perceived service quality, price, and promotion have a positive and significant impact on customer loyalty. Individually, perceived service quality and promotion have a greater influence than price. These findings provide insights into factors that can enhance customer loyalty and offer recommendations to the management of Café Njajan.co to continue improving service quality, set competitive prices, and develop more effective promotional strategies.